Search for Z ' resonances decaying to t(t)over-bar in dilepton plus jets final states in pp collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; et al. (2013)
A search for resonances decaying to top quark-antiquark pairs is performed using a dilepton+jets data sample recorded by the CMS experiment at the LHC in pp collisions at √s=7 TeV corresponding to an integrated luminosity of 5.0 fb-1. No significant deviations from the standard model background are observed. Upper limits are presented for the production cross section times branching fraction of top quark-antiquark resonances for masses from 750 to 3000 GeV. In particular, the existence of a leptophobic topcolor particle Z′ is excluded at the 95% confidence level for resonance masses MZ ′<1.3 TeV for ΓZ′=0.012MZ ′, and M<1.9 TeV for ΓZ′=0.10MZ ′. © 2013 CERN.